2023
DOI: 10.1590/1517-8692202329012022_0354
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Psychological Quality and Training in Basketball Players

Abstract: Introduction Psychological monitoring and psychological intervention of basketball players has been a focus of attention in sports training. In basketball, players consume much physical energy and also much mental energy. Psychological tension and emotional changes cause basketball players to restrict their technical abilities. Objective Analyze the relationship between sport-induced mental fatigue and pre-game emotions in basketball players. Methods This paper selects 40 basketball players as research volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Studies have indicated that athletes with high levels of drive and self-assurance are likelier to persevere in the face of difficulties and perform well under duress (Daub et al, 2023;Leonardi et al, 2019). Athletes can also overcome losses and stay focused during rigorous competition by strengthening their mental resilience through goal-setting, visualisation, and mindfulness training (Li & Ma, 2023;Mi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that athletes with high levels of drive and self-assurance are likelier to persevere in the face of difficulties and perform well under duress (Daub et al, 2023;Leonardi et al, 2019). Athletes can also overcome losses and stay focused during rigorous competition by strengthening their mental resilience through goal-setting, visualisation, and mindfulness training (Li & Ma, 2023;Mi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%